The Fate of Nanoparticles In Vivo and the Strategy of Designing Stealth Nanoparticle for Drug Delivery - Bao, Jianwei; Zhang, Qianqian; Duan, Tijie; Hu, Rongfeng; Tang, Jihui (Current Drug Targets, 2021)
Nano-drug delivery systems (Nano-DDS) offer powerful advantages in drug delivery and targeted therapy for diseases. Compared to the traditional drug formulations, Nano-DDS can increase solubility, biocompatibility, and reduce off-targeted side effects of free drugs. However, they still have some disadvantages that pose a limitation in reaching their full potential in clinical use. Protein adsorption in blood, activation of the complement system, and subsequent sequestration by the mononuclear phagocyte system (MPS) consequently result in nanoparticles (NPs) to be rapidly cleared from circulation. Therefore, NPs have low drug delivery efficiency. So, it is important to develop stealth NPs for reducing bio–nano interaction. In this review, we first conclude the interaction between NPs and biological environments, such as blood proteins and MPS, and factors influencing each other. Next, we will summarize the new strategies to reduce NPs protein adsorption and uptake by the MPS based on current knowledge of the bio–nano interaction. Further directions will also be highlighted for the development of biomimetic stealth nano-delivery systems by combining targeted strategies for a better therapeutic effect.
Keywords: Nanoparticles